Application of fuzzy logic in medical data interpretation (Bangladesh Journal of Scientific and Industrial Research, 2015)
This paper serves the purpose of presentation of a general view of the current applications of fuzzy logic in medicine and bioinformatics. Using fuzzy logic, we particularly review medical aspects. We then recall the geometrical interpretation of fuzzy sets as points in a fuzzy hypercube and present two concrete illustrations in medicine (drug addictions) and in bioinformatics (comparison of genomes). DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22127 Bangladesh J. Sci. Ind. Res. 49(3), 137-146, 2014